Analysis of the Development of Innovative Entrepreneurship for the Assess Their Competitiveness and Environmental Impact Factors - VIKULENKO, Julia; BELGIBAYEVA, Anargul; DENISSOVA, Oxana; ABAUOVA, Gulzhan; TULEMETOVA, Aigul; SADYKOVA, Rysty (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
The development of innovative processes reflects the general state of the economy and is conditioned by socio-economic transformations. The main context of these changes is associated with the formation of a new, entrepreneurial culture, the order and methods of coordination and interaction between the subjects of innovation. As a result, there is an active search for new paradigms corresponding to the ongoing changes in the period of integration and globalization of relations. Using statistical data on the development of SMEs in the Republic of Kazakhstan, authors posed and solved the problem of establishing such a relationship based on the results of using a complex index known as the index of structural-dynamic analysis, which is known in foreign literature as a “shift-share analysis” tool.